Failure to Replicate the Association Between Fractional Anisotropy and the Serotonin Transporter Gene (5-HTTLPR, rs25531) - Klucken, Tim; Tapia León, Isabell; Blecker, Carlo; Kruse, Onno; Stalder, Tobias; Stark, Rudolf (Frontiers in Behavioral Neuroscience, 2018)
Recent work underlines the importance of alterations in white matter (e.g. measured by fractional anisotropy) as a neural vulnerability marker for psychiatric disorders. In this context, the uncinate fasciculus (UF), which connects the limbic system with prefrontal areas, has repeatedly been linked to psychiatric disorders, fear processing, and anxiety-related traits. Individual differences in UF fractional anisotropy may partly be genetically determined. Variation in the promoter region of the serotonin transporter gene (serotonin transporter-linked polymorphic region [5-HTTLPR]) is a particularly promising candidate in this context, which has been linked to psychiatric disorders as well as to limbic and prefrontal reactivity. However, findings on the association between the 5-HTTLPR and fractional anisotropy within the UF-tract have been heterogeneous. The present study investigated this relationship and extended previous work by considering different genetic classification approaches as well as sex effects in a human sample (n=114). All participants were genotyped for the 5-HTTLPR and the rs25531 polymorphism. As a main result, we did not find any significant relationship between the 5-HTTLPR and fractional anisotropy in the UF-tract and in a control tract although power analyses showed an adequate power. In addition, genotype effects were neither found when different classification approaches were used nor when analyses were carried out in males or females only. The present findings suggest that the association of the 5-HTTLPR and fractional anisotropy seems to be a more labile phenomenon than previously assumed. Possible explanations and limitations are discussed.